Electrical and optoelectronic studies of semiconductor nanostructures - Wong, Jen It. (2012)
Electrical and optoelectronic properties of semiconductor nanostructures including silicon nanocrystals (nc-Si) and n-CdSxSe1-x nanowires have been studied in this thesis. Firstly, the current conduction in nc-Si embedded dielectric thin films of a metal-oxide-semiconductor (MOS) device with different nc-Si distributions in the gate oxide (i.e., SiO2) has been investigated. It was shown that Fowler-Nordheim (FN) injection from the Si substrate to the oxide and the nc-Si-assisted conductions (e.g., nc-Si-assisted direct tunneling/FN tunneling, Frenkel-Poole emission) contribute to the current conduction depending on both the nc-Si distribution and magnitude of the gate bias. Besides, current conduction of the metal-insulator-semiconductor (MIS) structure with different nc-Si concentrations embedded in Si3N4 thin films has been investigated and compared with pure Si3N4 thin films. It was shown that the pure Si3N4 thin film and the Si3N4 thin films embedded with nc-Si are dominated by different conduction mechanisms both at low and high electric fields. Moreover, the lateral charge transfer in an nc-Si layer embedded in SiO2 thin film has been demonstrated. If an nc-Si layer exists in the spacing regions between two MOS devices with nc-Si embedded in the gate oxide, the charging of one of the devices can induce a large flat-band voltage shift in the other device. Secondly, nc-Si non-volatile memory (NVM) devices have been fabricated with both low pressure chemical vapor deposition (LPCVD) and ion implantation method, and their memory characteristics have been studied. The nc-Si fabricated by LPCVD is promising for the NVM application, but it requires a high quality ultra-thin tunnel oxide, which is a challenge in the device fabrication. In order to circumvent the ultra-thin tunnel oxide issue, an alternative approach, i.e., the ion implantation technique is used. With this approach, the nc-Si depth profile in the gate oxide can be precisely controlled without the need of growing an ultra-thin tunnel oxide. Thirdly, a quasi-graded refractive index (n) anti-reflection coating (ARC) layer was fabricated in one step using conventional plasma enhanced chemical vapor deposition (PECVD) equipment. By embedding nc-Si in the ARC layers which can convert UV light to useful visible light, we can effectively use the wasteful and harmful UV radiation, and thus more solar energy can be used while the solar cell lifetime can be extended. The ARC is optimized so that it has a very low reflectance in the visible and near-infrared regions and a weak dependence on the incident angle. A 13.75% improvement in reflectance efficiency from the quasi-graded n ARC layer has been achieved as compared to the conventional Si3N4 anti-reflective layer. Finally, we have demonstrated that heterojunctions formed between n-CdSxSe1-x nanowires and the p+-SiC substrate can emit visible lights at room temperature in the wavelength range from yellow/orange to red under a constant voltage supply. Visible electroluminescence (EL) with tunable wavelengths has been observed at room temperature from randomly assembled n-CdSxSe1-x nanowires grown on p+-SiC substrate by vapor transport technique. The dominant emission peaks can be tuned from ~720 to ~520 nm by varying the composition of the alloy nanowires.